(untitled) (Hologramática, 2023)
In the contemporary field of study on the link between education and work, it is recognized that the training and labor insertion processes respond to multiple needs for an equitable economic, social and cultural development, which corresponds to a broad and inclusive conception of work pPublic policies aimed at social inclusion. In this sense, the article aims to provide knowledge about the link between education and work in the university through the analysis of the educational and labor trajectories of the graduates of the University School of Trades (EUO) of the National University of La Plata (UNLP). The methodological approach adopted is of a qualitative type, aimed at finding links and meanings between a set of data sources and conceptual contributions regarding the educational and labor trajectories of EUO graduates. We worked with a set of secondary data sources, both quantitative (statistical reports) and qualitative (interviews and accounts of its main protagonists), corresponding to the years 2011 to 2017. The conclusions from the analysis of trajectories allow an approximation to the conceptualization of the link between education and work, in this case, through a specific university training proposal. In this instance, it is possible to anticipate that the link is not necessarily linear or a priori, nor does it maintain an end reduced to economics dimensions.